Curcumin attenuates LPS-induced inflammation in RAW 264.7 cells: A multifaceted study integrating network pharmacology, molecular docking, molecular dynamics simulation, and experimental validation - Xiaojing Gong; Dingshan Xue; Hongyan Meng; Bing Xie; Lihua Zhao; Chuanhui Zang; Jingjing Kong (PLoS ONE, 2025)
Background Inflammation is a critical immune response that protects the body from infections and injuries. However, chronic inflammation can lead to diseases such as cancer. Curcumin, a bioactive compound extracted from Curcuma longa , has been widely studied for its anti-inflammatory properties. Despite extensive research, the comprehensive molecular mechanisms underlying curcumin’s anti-inflammatory effects, particularly its multi-target regulatory network, remain incompletely understood. This study aims to elucidate these mechanisms using an integrated approach combining network pharmacology, molecular docking, molecular dynamics simulation, and in vitro experimental validation. Methods We utilized network pharmacology to identify potential targets and pathways involved in curcumin’s anti-inflammatory effects. Molecular docking and dynamics simulation were conducted to evaluate the binding affinity and stability of curcumin with key inflammatory targets. The anti-inflammatory effects of curcumin were further validated in vitro using LPS-induced RAW 264.7 cells. Cell viability, NO content, and mRNA expression levels of pro-inflammatory cytokines ( IL-1β , IL-6, and TNF ) were assessed. Results Network pharmacology identified 135 potential targets for curcumin’s anti-inflammatory effects, with key pathways including TNF, HIF-1, PI3K-Akt, JAK-STAT, and MAPK signaling pathways. Molecular docking revealed strong binding affinities of curcumin with core targets such as IL-6, TNF, IL-1β, AKT1, and STAT3, with binding energies ranging from −6.2 to −7.5 kcal/mol. Molecular dynamics simulations demonstrated the stability of these complexes over a 100-nanosecond period. In vitro experiments showed that curcumin significantly reduced NO production and mRNA expression of IL-1β , IL-6, and TNF in LPS-induced RAW 264.7 cells, with optimal effects observed at a concentration of 125 μg/mL. Conclusion Our study provides a comprehensive understanding of curcumin’s anti-inflammatory mechanisms through an integrated approach. The findings highlight curcumin’s potential as a therapeutic agent for inflammatory diseases. However, further in vivo studies are necessary to fully elucidate its therapeutic efficacy and mechanisms of action.